UNGKAPAN BAHASA YANG BERMAKNA BUDAYA DALAM SISTEM BERCOCOK TANAM PADI SUB-ETNIK TONTEMBOAN - Mawara, Jetty E. T. (HOLISTIK, Journal Of Social and Culture, 2011)
From regional and its user point of view, Tontemboan language is the largest among the other vernacular languages in Minahasa. In practice, as the other vernacular languages, it is less frequently used, due to the progress of the community and of theÂ  propagation of Melayu Manado. The younger generation less and less speaks the language using Bahasa Indonesia for daily communication. Many expression denoting cultural value are found in the language. This cultural value may disappear when the language is not practiced anymore. One way to preserve this cultural value is by doing this kind of research. TheÂ  outcomes of the research are as the following: there are 6 step in the rice cultivation, i.e. (1) opening the land, (2) selecting the seed, (3) planting the seedling, (4) nursing the plant, (5) to crop, (6) making use of the crop.There are 40 expressions denoting cultural meaning which influence the way of thinking, i.e. appreciating time, working hard, helping each other, working together. The conclusion of the research is that through systematic steps, the Tontemboan farmers systematically work step by step, taking care of the land and plant, and have a plan to make use of their crop, meaning having a futurological view. Keywords : cultural, language, Tontemboan